Gander Sperm Cryopreservation in Plastic Straws - Bychko, S. V.; Artemenko, O. B.; Tereshchenko, O. V.; Linnik, T. P. (Problems of Cryobiology and Cryomedicine, 2004)
The authors determined the major zones of spermatozoa injuries during cryopreservation and the optimum rates for gander semen cooling at 0 to -196°C in plastic straws. At the initial stage of freezing down to –10°C the semen cooling was shown to be reasonable with the rate of 5°C/min, 50°C/min at further cooling –10 to –90°C, and –90 to –196°C with the cooling rate of 15°C/min. Morphological integrity of gander sex cells when freezing according to the method proposed was found to be 10-15% higher comparing to the standard one elaborated at the Institute for Poultry Research.